Dampak Pertambangan Nikel Terhadap Daerah Penangkapan Ikan di Perairan Kabupaten Halmahera Timur - Deni Sarianto; Domu Simbolon; Budi Wiryawan (Institut Pertanian Bogor, 2016)
East Halmahera District is one of the mining central areas Nickel in North Moluccas. This mining had a great impact on water quality changes. The aims of this study were to determine the content of Suspended Particulate Matter in East Halmahera waters, determine the water quality level, and determine fishing ground degradation level. The results showed the suspended solids in East Halmahera waters were above NAB, which had been set by Ministry of Environment those were less than 25 mg/l. While the average of SPM content in East Halmahera waters were above 25 mg/l except Wasile. The content of nickel in waters were known under NAB, but it had approached the NAB value which it means nickel had impacted the waters. Water quality changes had given impact to the fish degradation in waters, which the fish were captured by lift netwere classified in ilegal size (IS), that Stolephorus spp 62%, Loligo spp 67%. The number of IS for anchovy and squid were caused by lift net operation which were located near the coastal area where this area has been pressed by mining activities. This condition did not happen on purse seine and gillnet which legal size (LS) of Decaptrus spp 96% and Rastrilliger spp 90%. It was caused by fishing gear which operated far from coastal area. Based on the analysis, can be concluded that the mines Ni has a considerable effect on the degradation of water quality and reduction in size of a decent fish caught mainly lift nets.